MRAJ 2022
DOI: 10.18103/mra.v10i7.2901
|View full text |Cite
|
Sign up to set email alerts
|

Vinyl halogenated fatty acids display antibacterial activity against clinical isolates of methicillin-resistant Staphylococcus aureus

Abstract: Methicillin-resistant Staphylococcus aureus is a pathogen responsible for skin and wound infections, pneumonia, and bloodstream infections. Serious attention is needed because Methicillin-resistant S. aureus is also resistant to many other commonly used antibiotics. This study explores the potential of vinyl halogenated fatty acids as antibacterial agents. Specifically, the total synthesis of vinyl halogenated fatty acids was performed to investigate their antibacterial activity against clinical isolates of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…42 This work is the first report providing evidence that previously synthesized 2-alkynoic antibacterial fatty acids can be used as starting materials for the synthesis of novel analogs of C6-HSL (Figure 1) with the potential to inhibit QS-mediated mechanisms. 28,29,31,32 In this study, we synthesized three HSLs using synthetic strategies described in Schemes 1−3. Once these compounds were synthesized, the effect of HSL on bacterial cell growth and violacein production was investigated (Figure 2).…”
Section: ■ Discussionmentioning
confidence: 99%
“…42 This work is the first report providing evidence that previously synthesized 2-alkynoic antibacterial fatty acids can be used as starting materials for the synthesis of novel analogs of C6-HSL (Figure 1) with the potential to inhibit QS-mediated mechanisms. 28,29,31,32 In this study, we synthesized three HSLs using synthetic strategies described in Schemes 1−3. Once these compounds were synthesized, the effect of HSL on bacterial cell growth and violacein production was investigated (Figure 2).…”
Section: ■ Discussionmentioning
confidence: 99%
“…aureus (Fig. 15D) (Sanabria-Rios et al, 2022), and brominated derivatives of vinyl FAs were antileishmanial and inhibited topoisomerase IB enzyme of Leishmania sp. due to halogen bond formation (Carballeira et al, 2019).…”
Section: Lipidsmentioning
confidence: 93%
“…17). During this review, we observed that the majority of new and existing compounds functionalized with halogens had a greater affinity for Gram-positive bacteria and fungi than Gram-negative bacteria (Doyle et al, 2019;Sanabria-Rios et al, 2022). In addition, despite exhibiting excellent druglike properties, including blood-brain penetration and high GI absorption, Br-and Clsubstituted cyclohexanol benzo[b]thiophene derivatives lacked activity against Gramnegative bacteria at high doses (Masih et al, 2021).…”
Section: Bacterial Cell Typementioning
confidence: 99%
“…Bactericidal surfaces are generally obtained by use of quaternary ammonium compounds, , other cationic compounds , like PEI, bromides, chlorine containing compounds like triclosan and N-halamines, , silver and nanoparticles, other metal nanoparticles, carbon based materials like carbon nanotubes (CNT) and graphene and so on, each having their own method of action. Other than that, natural antibacterial polymers like chitosan and bioderived compounds like lignin, coumarin, and others can also be used.…”
Section: Functional Tengsmentioning
confidence: 99%